2011
DOI: 10.4049/jimmunol.1003020
|View full text |Cite
|
Sign up to set email alerts
|

The Danger Signal, Extracellular ATP, Is a Sensor for an Airborne Allergen and Triggers IL-33 Release and Innate Th2-Type Responses

Abstract: The molecular mechanisms underlying the initiation of innate and adaptive proallergic Th2-type responses in the airways are not well understood. IL-33 is a new member of the IL-1 family of molecules that is implicated in Th2-type responses. Airway exposure of naive mice to a common environmental aeroallergen, the fungus Alternaria alternata, induces rapid release of IL-33 into the airway lumen, followed by innate Th2-type responses. Biologically active IL-33 is constitutively stored in the nuclei of human airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
431
6
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(477 citation statements)
references
References 77 publications
33
431
6
3
Order By: Relevance
“…NH cells can produce large amounts of type-2 cytokines such as IL-5 and IL-13 in response to IL-33. Several groups have characterized populations of type-2 cytokine-producing ILCs associated with IL-33 mediate diseases in the lung [15][16][17][18][19][20][21] . However, it is unknown whether NH cells are involved in the observed corticosteroid sensitivity.…”
mentioning
confidence: 99%
“…NH cells can produce large amounts of type-2 cytokines such as IL-5 and IL-13 in response to IL-33. Several groups have characterized populations of type-2 cytokine-producing ILCs associated with IL-33 mediate diseases in the lung [15][16][17][18][19][20][21] . However, it is unknown whether NH cells are involved in the observed corticosteroid sensitivity.…”
mentioning
confidence: 99%
“…IL-33 is released from epithelial cells on exposure to allergens and is crucial for the process of allergic sensitization (21,22). IL-33 recruits type 2 innate lymphoid cells (ILC2s), which express the transcription factor GATA3 and produce IL-13 and IL-5, much like helper T type 2 cells (23,24).…”
mentioning
confidence: 99%
“…In addition, when the cells were exposed to HDM, IL-25 protein was detected predominantly in the cytoplasm ( Figure 3B). Endogenous ATP and engagement of purinergic receptors plays a pivotal role in IL-33 release by NHBE cells (25). Extracellular release of IL-25 protein was also partially but significantly inhibited by global antagonists for purinergic receptors, including oxidized ATP and suramin ( Figure 3C).…”
Section: Il-25 Is Actively and Rapidly Released Without Apparent Cellmentioning
confidence: 93%
“…In a previous study, we found that an IL-1-family cytokine, IL-33, is constitutively produced and stored in nuclei of NHBE cells. Extracts of certain allergens, but not LPS, stimulated extracellular release of this stored IL-33 (25). Therefore, we suspected that IL-25 might be regulated similarly to IL-33.…”
Section: Il-25 Protein Is Detectable In Resting Aecsmentioning
confidence: 94%